What may we hope? - Jackelén, Antje (Dialog, 2022)
Christians are a people of hope. There is no other alternative after Jesus Christ overcame the power of death through his resurrection. “Rejoice in hope, be patient in suffering, persevere in prayer,” Paul encourages the congregation in Rome (Romans 12:12). The author of 1 Peter is conscious that hope is no mere feeling. Like faith and love, hope is a gift. But hope is also a choice that is based on realities, a virtue if you like. For this reason, “always be ready to make your defense to anyone who demands from you an accounting for the hope that is in you; yet do it with gentleness and reverence. Keep your conscience clear.” (1 Peter 3:15–16). Keeping silent about hope is to deceive. Speaking of hope when humankind is shuttered in crisis requires both clear mind and pastoral empathy. Otherwise speaking of hope may sound as an escape from reality, a superficial consolation, or even cynicism. We need to ask: how is hope a power that prevails in worldly adversities?